Graphene functionalised by laser-ablated V2O5 for a highly sensitive NH3 sensor - Kodu, Margus; Berholts, Artjom; Kahro, Tauno; Kook, Mati; Ritslaid, Peeter; Seemen, Helina; Avarmaa, Tea; Alles, Harry; Jaaniso, Raivo (Beilstein Journal of Nanotechnology, 2017)
Graphene has been recognized as a promising gas sensing material. The response of graphene-based sensors can be radically improved by introducing defects in graphene using, for example, metal or metal oxide nanoparticles. We have functionalised CVD grown, single-layer graphene by applying pulsed laser deposition (PLD) of V2O5 which resulted in a thin V2O5 layer on graphene with average thickness of ≈0.6 nm. From Raman spectroscopy, it was concluded that the PLD process also induced defects in graphene. Compared to unmodified graphene, the obtained chemiresistive sensor showed considerable improvement of sensing ammonia at room temperature. In addition, the response time, sensitivity and reversibility were essentially enhanced due to graphene functionalisation by laser deposited V2O5. This can be explained by an increased surface density of gas adsorption sites introduced by high energy atoms in laser ablation plasma and formation of nanophase boundaries between deposited V2O5 and graphene.
Keywords: ammonia; electric conductivity; gas sensor; graphene; pulsed laser deposition; UV light activation; vanadium(V) oxide